UNDERSTANDING NORTHERN GHANAâ€™S CONTEMPORARY CHIEFTAINCY CONFLICTS: ORIGINS, ACTORS AND DYNAMICS - Ibrahim, M. G.; Ateng, M. A.; Akanyani, F. A. (UDS International Journal of Development, 2025)
Despite the countless efforts to address chieftaincy conflicts in Northern Ghana, these conflicts remain protracted, relapsed, and internecine. This paper, examined these kinds of conflicts by illustrating a comprehensive understanding of the contemporary conflicts in Northern Ghana. The research strategy for this study is qualitative research, while the study design is the multiple case study. Interviews and focus groups were used to gather data from 39 respondents who were chosen purposively. The findings from the thematic and cross-site analysis indicated that conflicts were predominantly characterized by a structural condition where both sides not only used history to support their perspectives, but also manipulated history in specific ways. The various iterations of historical accounts often offer a consistent justification for the refusal to accept practical compromises. Furthermore, although the skins were associated with chieftaincy, the underlying motivations and interests were primarily connected to obtaining and managing the land resource. The presence of contextual concerns leads to a syndrome of conflict that has a substantial impact on the conflict management strategies used to address various conflict situations. These qualities are crucial for establishing a tranquil environment as they provide a foundation for managing activities effectively.Â  Keywords: Conflicts, Protracted, Relapsed, Contemporary, Mechanisms, Ghana